Haze impact on availability of terrestrial free space optical link - Basahel, Ahmed; Islam, Md. Rafiqul; Ahmad Zabidi, Suriza; Habaebi, Mohamed Hadi (IEEE, 2016)
Free Space Optics is a promising optical wireless technology in broadband networks. It uses laser as a medium of transmission between two transceivers. In tropical climate, haze is one of the weather phenomenons which reduce the visibility. Low visibility increases atmospheric attenuation and reduce the availability of optical signals for free space optics (FSO) links. In this paper, the effect of atmospheric attenuation due to haze on free space optical link in tropical climate has been demonstrated. The analysis based on one year measured visibility data in Malaysia. Predicted attenuation varies with different wavelengths. Thus, two wavelengths were considered. The predicted atmospheric attenuation was compared across the two wavelengths. Measured visibility data and predicted attenuation were used to estimate the link availability of free space optical links. From the results higher wavelength has lower attenuation compare with lower wavelength. This paper indicates useful information for the deployment of FSO link in tropical climate.